Jejak Ekologis Kawasan Regional Bandung - Marganingrum, Dyah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTThis paper aims to explain the application of Ecological FootprintÃ‚Â method as an approach for finding out the carrying capacity of the region. Case study was conducted in Bandung Basin Area that called as The Bandung Regional area. Ecological Footprint Analysis was done by using the Workbook and Guidebook National Footprint Account 2008 that prepared by the Global Footprint Network (GFN). Results of the analysis showed that the ecological footprint of Bandung Regional has been deficit of 1.31 gha/capita (EF Consumption is 1.37 gha/capita and biocapacity is 0.06 gha/capita). Thus, the supply-demand ratio is 0.04. This value ratio is less than one so it is categorized as the overshooting status. This status indicates that the carrying capacity of resources has been overloaded in the Bandung Regional. Therefore, it requires the number of efforts including regulation that can alter the consumption pattern and create metabolic utilization of natural resources which is more circular than linear. In addition, it needs a good cooperation among stakeholders in the surrounding area of Regional Bandung to meet the demands of all communities in Bandung region.Keywords: Bandung regional, carrying capacity, ecological footprint, overshootÃ‚Â ABSTRAKMakalah ini bertujuan menjelaskan hasil aplikasi metode jejak ekologis sebagai salah satu pendekatan untuk mengetahui daya dukung lingkungan suatu kawasan. Studi kasus dilakukan di Kawasan Cekungan Bandung yang disebut juga sebagai Regional Bandung. Analisis jejak ekologis dilakukan dengan memanfaatkan WorkbookÃ‚Â dan Guidebook National Footprint AccountÃ‚Â Tahun 2008 yang disediakan oleh Global Footprint NetworkÃ‚Â (GFN). Hasil analisis menunjukkan bahwa jejak ekologis Regional Bandung mengalami defisit sebesar 1.31 gha/kapita dengan nilai jejak ekologis konsumsi (EF consumption) sebesar 1.37 gha/kapita dan biokapasitasnya sebesar 0,07 gha/kapita. Dengan demikian rasio supply-demandÃ‚Â sebesar 0.04. Nilai rasio supply-demand kurang dari satu dikategorikan sebagai status overshoot. Status ini mengindikasikan bahwa daya dakung sumber daya alam di kawasan Regional Bandung telah terlampaui. Oleh karena itu diperlukan berbagai upaya termasuk regulasi yang dapat merubah pola konsumsi dan menciptakan metabolisme pemanfaatan sumber daya alam yang lebih bersifat sirkuler daripada linier. Selain itu perlu dilakukan kerjasama yang baik diantara pemangku kepentingan di wilayah sekitarnya untuk memenuhi segala kebutuhan masyarakat di Regional Bandung.Ã‚Â Kata kunci: daya dukung, jejak ekologis, regional Bandung, terlampaui